Дослідження палеолітичних пам’яток експедицією НаУКМА на Кіровоградщині у 2008 р. - Залізняк, Л.Л.; Вєтров, Д.О.; Беленко, М.М. (Археологічні дослідження в Україні, 2010)
Brief information on the research of the Upper Palaeolithic sites Vys and Troyanove 4 near the town of Novomyrhorod in Kirovohrad region conducted by the expedition of the National University of Kyiv-Mohyla Academy in 2008 is presented.